2012
DOI: 10.1002/pon.3106
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of general self‐efficacy with anxiety, symptom severity and quality of life in cancer patients before and after radiotherapy treatment

Abstract: A sense of self-efficacy and its relationship with anxiety, symptom distress and quality of life are important factors for patients receiving radiotherapy. Health care professionals need to be aware of anxiety, symptom severity and patient's quality of life prior to treatment initiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 64 publications
2
39
0
5
Order By: Relevance
“…Compared with the negative and inevitable factors mentioned above, positive psychological variables (hope, optimism and self-efficacy) may be secondary to depression and anxiety of cancer patients. Although some studies explored the impacts of positive psychological variables on depression and anxiety among cancer patients [17], [23], [31], the possibility that reduced hope, lower optimism and reduced self-efficacy may be also the potential causes of depression and anxiety did not receive much consideration. Therefore, in addition to discussing the prevalence and associated clinic variables of depression/anxiety among cervical cancer patients, we also mainly explored the effects of hope, optimism and self-efficacy on depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Compared with the negative and inevitable factors mentioned above, positive psychological variables (hope, optimism and self-efficacy) may be secondary to depression and anxiety of cancer patients. Although some studies explored the impacts of positive psychological variables on depression and anxiety among cancer patients [17], [23], [31], the possibility that reduced hope, lower optimism and reduced self-efficacy may be also the potential causes of depression and anxiety did not receive much consideration. Therefore, in addition to discussing the prevalence and associated clinic variables of depression/anxiety among cervical cancer patients, we also mainly explored the effects of hope, optimism and self-efficacy on depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, hope, optimism and general self-efficacy showed significantly independent effects on depression when they entered into regression together, indicating that hope, optimism and general self-efficacy as a whole might alleviate depression by enabling patients to establish positive, realistic and desired goals, have confidence to achieve the given goals and recognize the interdependent influence of others (hope) [17], [21], to expect positive health-related outcomes in the future and maintain the efforts to attain the realistic and achievable outcomes (optimism) [24], [26], to mobilize the resources required to positively manage or combat the physical and psychological challenges of cancer (general self-efficacy) [28][31]. These findings leaded us to believe that both positive outlooks regarding one's own goal, life and family/friends (hope), positive expectancies regarding favorable outcomes in one's own future (optimism), and positive beliefs regarding one's own ability to deal with the challenges (general self-efficacy) were important to successfully alleviate and even overcome depression in cervical cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Concerning the influence of radiotherapy on the psychophysiological state, a study reported that there was a correlation between QOL/symptom deterioration and anxiety/depression [16] [17]. However, no study has examined palliative radiotherapy.…”
Section: Discussionmentioning
confidence: 99%